Step-by-step approach: stereotaxic surgery for in vivo extracellular field potential recording at the rat Schaffer collateral-CA1 synapse using the eLab system - Azimzadeh, Mansour; Mohd Azmi, Mohd Amirul Najwa; Reisi, Parham; Cheah, Pike-See; Ling, King-Hwa (Elsevier, 2024)
In vivo extracellular field potential recording is a commonly used technique in modern neuro- science research. The success of long-term electrophysiological recordings often depends on the quality of the implantation surgery. However, there is limited use of visually guided stereotaxic neurosurgery and the application of the eLab/ePulse electrophysiology system in rodent models. This study presents a practical and functional manual guide for surgical electrode implantation in rodent models using the eLab/ePulse electrophysiology system for recording and stimulation pur- poses to assess neuronal functionality and synaptic plasticity. The evaluation parameters included the input/output function (IO), paired-pulse facilitation or depression (PPF/PPD), long-term po- tentiation (LTP), and long-term depression (LTD).